The Influence of Instagram Social Media Marketing and Consumer Behavior on the Purchase Decision of Orchid Ornamental Plants at Yusra Florist (Phalaenopsis) Florist - Dia Ovitri Agustin; Khafi Puddin (CV. Civiliza Publishing, 2026)
This study aims to analyze the influence of Instagram social media marketing and consumer behavior on the purchase decision of orchid ornamental plants (Phalaenopsis) at Yusra Florist Medan Flower Shop. The research method used is a descriptive qualitative approach with a type of field research. Primary data was collected through observation, documentation, and in-depth interviews with six selected informants using purposive sampling techniques, consisting of store owners, sales staff, and customers. Data analysis applies the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that marketing through the Instagram account @yusraflorist_medan.orchid is very effective in expanding the market reach and triggering consumer visual interest through regular product photo and video uploads. Meanwhile, consumer behavior is dominated by the middle and upper class of people who prioritize plant quality, aesthetic value, prestige, and service satisfaction over price sensitivity. The main obstacle found was the limited admin response (slow response) due to dual tasks. In conclusion, the synergy between attractive product visualizations on Instagram and the consistency of direct and digital service quality has proven to be crucial factors that shape customer trust and determine repurchase decisions at Yusra Florist Stores.